KAJI BANDING FERTILITAS DAN PERIODE FERTIL AYAM BANGKOK DENGAN AYAM PELUNG - Junaedi Junaedi; Nurcholis Nurcholis (Faculty of Agriculture, Musamus University, 2018)
This study aims to compare fertility and fertile periods between Pelung chickens and Bangkok chickens. The tools used in the study included semen collection equipment and hatchery equipment. The materials used in the study were infusion solution (Ringer Lactate), 4 Pelung male chickens and 4 Bangkok chicken studs. Semen is collected from 4 pelung chicken hens and 4 Bangkok chicken males. The collected semen is then diluted with 1: 3 ringer lactate. The semen that has been diluted with ringer lactate is inseminated in laying hens. Analysis of the data used is the T Test to compare fertility and fertile periods of Pelung chicken with Bangkok chickens. Spermatozoa fertility from artificial insemination (IB) Bangkok chicken 92.23 ± 2.5% and Pelung chicken 85.45 ± 3.8%. The fertile period average yield of IB Pelung chicken is 15.65 ± 1.5 days and Bangkok chicken is 13.67 ± 1.2 days. Spermatozoa fertility produced by artificial insemination (IB) of Bangkok chickens is higher than that of Pelung chicken spermatozoa. The fertile period average yield of IB Pelung chicken is higher than that of Bangkok chicken.